PERSEPSI UMAT TERHADAP PROGRAM PENGEMBANGAN SOSIAL EKONOMI DI PAROKI SANTO HILARIUS KLEPU-PONOROGO - Natalis Sukma Permana (Bahasa Indonesia, 2019)
Universal Church concerns deeply to social-economic problem of human race. Social Doctrine of The Church then appears as a way to solve social-economic problems of human race. That is why, the Indonesian apostolates attends in a ocial-economic Development (PSE) where it has been depeloped at all dioceses. Although, the development of socio-economic program is not supported well, but nowdays, Klepu-Ponorogo St. Hilary Parish has been traying to develope this program. They have some kinds of social-economic developments program such as: farming training school, home industry, organic rice farming, barns, mushrooms cultivation, urine liquid fertilizer. Eventhough, practically, they find some problems different interests on PSE program. It is actually influenced by the ineffectiveness of the program socialization to the whole people. Another factor is that, the people has not been yet interested to join in the program.